SHEBER PEDAGOG QANDAY BOLÍWÍ KEREK? - Ernazarov, N.E. (SCIENCE and SOCIETY, 2021)
The article deals with such issues as the teacher's needs in pedagogical skills, the ability to communicate with students on the basis of pedagogical skills, the formation of a teacher's friendly attitude towards students and the creation of a healthy environment for improving the quality of education. There is presented the characteristics corresponding to the modern teacher.